A Quantitative Study on the Effectiveness of Open Educational Resources (OER) in Enhancing Creative Thinking Skills - Sedayu, Agung; Herpratiwi, Herpratiwi; Yuliyanti, Dwi; Distrik, I Wayan (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aims to provide empirical evidence on the effectiveness of Open Educational Resources (OER) in facilitating transformative learning experiences that enhance students' creative thinking skills. A quantitative approach was employed for the study, wherein two groups, experimental and control, underwent pre-tests and post-tests to measure variables such as fluency, flexibility, elaboration, and evaluation of their creative thinking abilities. The study revealed significant differences between pre-test and post-test scores for both groups, particularly in the indicators of flexibility and evaluation. However, diverse outcomes were observed when examining n-gain scores across all indicators of creative thinking skills, suggesting that the effectiveness of OER in facilitating transformative learning varies depending on the specific creative thinking indicators measured. The research emphasizes that while OER can facilitate transformative learning processes, it may not yield uniform results across all dimensions of creative thinking. The obtained results indicate no significant difference in flexibility. Contradictory conditions can be observed in fluency, elaboration, and evaluation indicators, showing significant differences. Therefore, educators should adopt varied approaches when integrating OER into their curricula to maximize the potential benefits of enhancing students' creative thinking skills. For future research, it is highly recommended to focus on the effectiveness of OER based on the type of content or subject matter taught to identify the most effective sources. Further research is also needed to compare the effectiveness of OER with other teaching methods.